Investigating the effect of frother type on froth structure, froth recovery and entrainment - Marozva, Tafadzwa (Department of Chemical Engineering, 2015)
Mineral processing involves liberation and beneficiation operations. Several beneficiation processes exist and one such important process is froth flotation. The flotation process involves the transportation of valuable minerals of a hydrophobic nature into the froth and to the concentrate launder. This hydrophobicity may be natural or imparted by a collector. Froth structure is significant in determining the froth stability which has an effect on the grade and recovery of valuable minerals. The froth structure is dependent on amongst other factors the type of frothers used during the separation process. As a result, frother type and concentration can be used to manipulate the froth recovery and grade of valuable mineral recovered. Upper Group 2 (UG2) ore contains chromite minerals which are naturally hydrophilic. The chromite minerals are usually recovered in the concentrate mainly due to entrainment. This lowers the grade of valuable minerals recovered and poses detrimental effects to downstream operations. Thus, the froth structure plays an important role in the flotation performance of UG2 ore. This project was aimed at investigating the effect of chain length and functional group of different frothers on the froth stability, froth recovery and entrainment. Froth recovery, entrainment, solids and water recovery, as well as metallurgical recovery, were measured in a laboratory scale continuous column flotation cell. Froth stability was measured in a froth stability column, which is a non-overflowing column in which froth rise rate and equilibrium height were measured. A series of increasing molecular weight polyglycol and alcohol frothers, and their blends, were used to investigate the effect of frother type on froth structure.